2011
DOI: 10.1002/app.34533
|View full text |Cite
|
Sign up to set email alerts
|

Study of chitosan and its derivatives as preservatives for field natural rubber latex

Abstract: In this study, the chitosan and its derivatives were tested for their preservative activities for field natural rubber (NR) latex. A series of chitosans with different molecular weights were obtained by nitrous acid depolymerization. The chemically modified chitosans, Ncarboxymethyl chitosan (NCMCh), N-sulfated chitosan (NSCh), and N-(2-hydroxy)propyl-3-trimethylammonium chitosan chloride (NHTACh), were prepared from high and low-molecular weight chitosans. Preservative activities for field NR latex of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Bacteria and enzyme degra-dation products will destroy the protective coating of NRL particles, reducing their stability [6,7]. Furthermore, the formation of fatty acids, which neutralize alkaline substances and decrease pH value [8], reduces particle repulsion [9][10][11], resulting in adhesion and aggregation development between rubber particles. Furthermore, it can reduce latex colloid stability, causing fast solidification and rot of NRL [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria and enzyme degra-dation products will destroy the protective coating of NRL particles, reducing their stability [6,7]. Furthermore, the formation of fatty acids, which neutralize alkaline substances and decrease pH value [8], reduces particle repulsion [9][10][11], resulting in adhesion and aggregation development between rubber particles. Furthermore, it can reduce latex colloid stability, causing fast solidification and rot of NRL [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported the development of the various preservatives systems that could inhibit the activity of bacteria in the latex and retard the chemical reaction of multivalent metal ions [8,9]; however, it suffered from certain disadvantages such as a gradual fall in the pH of the latex when stored for over a long period. Formaldehyde-based preservatives latex thickens with age and thus becomes unmanageable.…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al fabricated a continuous framework network of CMCs, which endowed epoxidized NR (ENR) with better mechanical properties and conductive ability when the moisture content was higher than 1%. Loykulnant et al prepared antibacterial NR composites with chitosan. However, it is noteworthy that the aforementioned natural polymers have relatively longer chains, whose common interactions such as twisting and folding of the macromolecular chains shield every part of reactive groups in the solid state.…”
Section: Introductionmentioning
confidence: 99%